Klasifikasi Sentimen Masyarakat Terhadap Proses Pemindahan Ibu Kota Negara (IKN) Indonesia pada Media Sosial Twitter Menggunakan Metode Naïve Bayes - Moch. Reinaldy Destra Fachreza; Suhartono Suhartono; M. Ainul Yaqin (UIN Sunan Kalijaga Yogyakarta, 2023)
Some time ago, the House of Representatives passed Law (UU) Number 3 of 2022 concerning the National Capital City on January 18, 2022. Then, President Joko Widodo officially signed the IKN Law on February 15, 2022. Thus, the Indonesian capital will be moved to Penajam Paser Utara Regency and Kutai Kartanegara Regency, East Kalimantan Province. The public's response to the decision varies; many respond with supportive sentiments, but some react with unsupportive ideas. Nowadays, there are many ways to observe information collected on social media. Various responses submitted through social media can be used as sentiment classification research data. The Naïve Bayes method is commonly used for this type of research. Data was collected between February 15-25, 2023, with as many as 500 tweets. This research uses the Gaussian Naïve Bayes type because of the independence assumption made by this method. Features that do not significantly contribute to the classification can be ignored, thus reducing the impact of irrelevant features. This study aims to measure public sentiment on Twitter towards the process of moving the nation's capital. The system created provides the best trial results at 80% feature usage with 82.0% accuracy, 76.9% precision, and 100% recall.